Michał Kazimierz Radziwiłł „Rybeńko” jako uczeń - Kucharski, Adam (Biuletyn Historii Wychowania, 2024)
Michał Kazimierz Radziwiłł, nicknamed “Rybeńko” (1702–1762), was a prominent representative of a Lithuanian–Polish magnate family in the 18th century. However, researchers have yet to portray his activities as a learner and a respective study is in high demand. A wealth of preserved historical sources: a journal and letters, allow to learn more and describe the course of his studies. The young magnate received only home education and went on a youthful educational journey (a grand tour), like many of his magnate peers. What emerges from the autobiographical notes is a picture of the learning process and relationships with the teachers. However, the skills he acquired and the average level of education did not have a profound impact on his political and military career, which was made possible by his social background.